1984
DOI: 10.1042/bj2200739
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in the fraction of 3-hydroxy-3-methylglutaryl-CoA reductase in the active form in rat liver microsomal fractions

Abstract: 'Initial' and 'total' activities of 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CoA reductase) were measured in cold-clamped samples of liver from rats at 2h intervals throughout the 24h light/dark cycle. Initial activities were obtained in microsomes (microsomal fractions) isolated and assayed in the presence of 100mM-KF, whereas 'total' activities were measured in microsomes prepared from the same homogenates but washed free of KF and incubated with exogenous partially purified rat liver protein phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…700-lOOO-fold to a final specific activity of 30-50 units/mg: details of the purification will be published elsewhere. Rat liver microsomes were prepared as described in [17]. HMG-CoA reductase-overproducing hamster cells (UT-l cells) were grown in roller bottles in 40 PM compactin [18].…”
Section: Methodsmentioning
confidence: 99%
“…700-lOOO-fold to a final specific activity of 30-50 units/mg: details of the purification will be published elsewhere. Rat liver microsomes were prepared as described in [17]. HMG-CoA reductase-overproducing hamster cells (UT-l cells) were grown in roller bottles in 40 PM compactin [18].…”
Section: Methodsmentioning
confidence: 99%
“…Rats were anaesthetized (60 mg of pentobarbitone/kg body wt.) 20 min before liver sampling; stress was lessened by handling of the animals for 5-7 days before the experiments (see Easom & Zammit, 1984b). No systematic study of the effects of anaesthesia on reductase activity was undertaken.…”
Section: Animalsmentioning
confidence: 99%
“…However, in these latter studies the E/T activity ratios observed for saline-treated (control) animals were very low (< 15%) and outside the physiological range (Easom & Zammit, 1984b. Consequently, a re-evaluation of the effects of glucagon on hepatic HMG-CoA reductase activity in vivo is required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations